NILAI-NILAI PENDIDIKAN ISLAM DALAM TRADISI FANTEN DI PATANI HALMAHERA TENGAH - Sarmi Sarmi; Surahman Amin; Indria Nur (Transformasi : Jurnal Kepemimpinan & Pendidikan Islam, 2022)
Value is not something we see from the world based on what we know, but value is more related to what should happen. Islamic education is a process of changing individual behavior for the better, so the value of Islamic education is the things or traits inherent in Islamic education that are used as a basis or life guide to become a better person. Islam recognizes the existence of community customs because customs are part of that society. In addition, customs or traditions often contain values whose source is the religion adopted or Islamic education. So the purpose of this study is to explore the values of Islamic education contained in the fanten tradition carried out by the Patani community of Central Halmahera every month of Rabiul Awal as an expression of gratitude for the birth of the Prophet Muhammad. So it can be understood that in the fanten tradition there is a process for strengthening faith, worship and morals which are the values of Islamic education